Rhinovirus Infection Drives Complex Host Airway Molecular Responses in Children With Cystic Fibrosis - Ling, Kak-Ming; Garratt, Luke W.; Gill, Erin E.; Lee, Amy H. Y.; Agudelo-Romero, Patricia; Sutanto, Erika N.; Iosifidis, Thomas; Rosenow, Tim; Turvey, Stuart E.; Lassmann, Timo; Hancock, Robert E. W.; Kicic, Anthony; et al. (Frontiers in Immunology, 2020)
Early life viral infections are responsible for pulmonary exacerbations that can contribute to disease progression in young children with CF. The most common respiratory viruses detected in the CF airway are human rhinoviruses (RV) and augmented airway inflammation in CF has been attributed to dysregulated airway epithelial responses, although evidence has been conflicting. Here, we exposed airway epithelial cells from children with and without CF to RV in vitro. Using RNA-Seq, we profiled the transcriptomic differences of CF and non-CF airway epithelial cells at baseline and in response to RV. There were only modest differences between CF and non-CF cells at baseline. In response to RV there were 1442 and 896 differentially expressed genes in CF and non-CF airway epithelial cells respectively. The core antiviral responses in CF and non-CF airway epithelial cells were mediated through interferon signaling although type 1 and 3 interferon signaling when measured, were reduced in CF airway epithelial cells following viral challenge consistent with previous reports. The transcriptional responses in CF airway epithelial cells were more complex than in non-CF airway epithelial cells with diverse over-represented biological pathways such as cytokine signaling and metabolic and biosynthetic pathways. Network analysis highlighted that the differentially expressed genes of CF airway epithelial cells transcriptional responses were highly interconnected and formed a more complex network than observed in non-CF airway epithelial cells. We corroborated observations in fully differentiated air-liquid interface (ALI) cultures, identifying genes involved in IL-1 signaling and mucin glycosylation that are only dysregulated in the CF airway epithelial response to RV infection. These data provide novel insights to the CF airway epithelial cells responses to RV infection and highlight potential pathways that could be targeted to improve antiviral and anti-inflammatory responses in CF.